OLD AND NEW PROBLEMS IN THE BALKANS AND MARXISM - Türkeş, Mustafa (Politeia, 2019)
Efforts to determine the place of Marxism in the Balkans in a historical manner seem to enable us to outline not only the historical importance of Marxism but also to point out more precisely its relevance with contemporary problems and possible solutions in the Balkans. In order to outline very briefly the place of Marxism in the Balkans, this paper first seeks to discuss the old (late 19th, early 20th) and new (late 20th, early 21st century) common problems people in the Balkans encountered with a view to underlining the continuity of the problems. Second, it illustrates the way in which the old and new problems had been addressed. I assume that capitalism keeps failing to find a workable solution to any major problem people in the Balkans faced, but constantly transforms the problems with which it overcomes its own survival. Third the paper examines achievements and shortcomings of first and second generation of socialists in the Balkans. Finally, the paper puts forward that it is up to the third generation of Marxist-inspired thinkers to propose an alternative system inspired from Marxism(s) as opposed to the capitalist system that kept failing to address the problem, but transforms the problem itself rather than solving any.
Keywords: Capitalism; Balkans; Marxism; old and new problems; socialists; transformation of the problems